The Effect Of Mentoring Programs On Improving Critical Thinking Ability Using Standardized Nursing Language As A Learning Method In Students - Anti Khaerunnisa; Antonius Rino Vanchapo; Neng Yulianti (Journal for Quality in Public Health, 2023)
Nursing mentoring is method appropriate in increase culture safety patient . Culture safety patient need developed more Formerly For can overcome concern. Describe the influence of mentoring programs on enhancement ability think critical use standardized nursing language as a learning method for students . In this study the researchers used the Quasi Experimental method with the One Group Pretest-posttest design approach , the population in this study were students of the Faathir Husada Tangerang College of Health Sciences semesters 4, 6, 8 with a total of 34 respondents. characteristics respondent based on type sex from 34 respondent type sex Woman the most with frequency 21 respondent . In research This analysis univariate used For know percentage from each variable research . Namely Program mentoring And Think Critical to student in STIKes Fathir Husada Tangerang. From the results research that has done exists influence positive and significant before and after given a mentoring program ability think critical use standardized nursing language .